Flaccid paralysis and abdominal pain, an approach to porphyrias: a literature review and case series - Nieto González, Manuel Alejandro (2021)
Porphyrias are inherited metabolic disorders caused by enzymatic deficiencies of HEM group biosynthesis. Most common in childhood at the third and fourth decade of life. They are characterized by increased levels of porphyrins, and various cutaneous, neurological, and visceral manifestations. We describe a series of 3 cases of female patients in the third decade of life with abdominal pain and a wide range of clinical manifestations and short and long-term complications. Our review contributes to the early recognition of these diseases to establish early specific managements to impact on irreversible outcomes.